Pengembangan Flipbook Digital pada Materi Makanan dan Sistem Pencernaan Kelas VIII SMP/MTs - A’yun, Tiara Nissa; Titin, Titin; Yeni, Laili Fitri (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Technology-based learning media is an innovative teaching approach that teachers can employ in the learning process. This developmental research aims to assess the feasibility and student response to digital flipbook media using Flip PDF Corporate Edition on the topic of food and digestive systems developed as a learning media for eighth-grade students at SMP Negeri 25 Pontianak. The research method employed is research and development using the ADDIE model. However, this study encompassed only four stages: analysis, design, development, and implementation. The data sources for this research included 15 eighth-grade students from SMP Negeri 25 Pontianak, three Biology teachers from SMP Negeri 25 Pontianak, SMP Negeri 17 Pontianak, and SMP Negeri 04 Sungai Raya, as well as two lecturers from the Department of Biology Education, Faculty of Teacher Training and Education, Tanjungpura University. The validation results of the digital flipbook media yielded a validity score (v) of â‰¥ 0.87, classified as valid. The inter-rater reliability using ICC obtained a score of 0.737, classified as moderate to good. The student response to the digital flipbook media resulted in a score of 91.11%, classified as very good.